Chimeric Fusion between Clostridium Ramosum IgA Protease and IgG Fc Provides Long-Lasting Clearance of IgA Deposits in Mouse Models of IgA Nephropathy. Issue 5 (May 2022) - Xie, Xinfang; Li, Jingyi; Liu, Pan; Wang, Manliu; Gao, Li; Wan, Feng; Lv, Jicheng; Zhang, Hong; Jin, Jing
Significance Statement: IgA nephropathy is the most common glomerulonephritis worldwide and a leading cause of kidney failure. The disease often progresses through episodes of flare-ups that require effective treatments to tame inflammation. We followed a rational design strategy to construct a recombinant fusion IgA protease derived from commensal gut microbiota Clostridium ramosum . The fusion protease, referred to as Fc-AK183, showed week-long activity in mice to completely obliterate IgA in circulation and clear pathologic deposits in the kidney. Therefore, the recombinant enzyme is a promising drug candidate for future treatment of IgA nephropathy. Visual Abstract: Abstract : Background: IgA nephropathy is a common primary glomerulonephritis caused by mesangial deposition of poly-IgA complexes. The disease follows a variable course of clinical progression, with a high risk of kidney failure. Although no specific therapy is available, enzymatic strategies to clear IgA deposits are being considered for the treatment of rapidly progressive IgA nephropathy. Methods: We chose an IgA protease of commensal bacterium Clostridium ramosum, termed AK183, as the template for constructing a recombinant biologic. To extend the t 1/2 in blood, we fused AK183 to the Fc segment of human IgG1. Activities of this Fc-AK183 fusion protein toward the cleavage and subsequent clearance of IgA were tested in mouse models. Results: First, we discovered an autocleavage activity of AK183 that separates the N-terminal protease from its C-terminal autotransporter β domain. Therefore, we grafted Fc to the N terminus of AK183 and demonstrated its week-long enzymatic activity in mice. In addition, the proteolytic fragments of IgA generated in the reaction with Fc-AK183 were effectively removed from circulation via kidney filtration. The combined actions of Fc-AK183-mediated cleavage and subsequent renal clearance of IgA resulted in a lasting obliteration of blood IgA, as demonstrated in a human IgA-injection model and in a humanized α1KI transgenic model. Fc-AK183 was also able to remove chronic IgA and associated complement C3 deposits in the glomerulus. Conclusion: We constructed a chimeric fusion of IgA protease with Fc and demonstrated its long-lasting efficacy as a promising targeted therapy for IgA nephropathy in mouse models.